|
In predicate logic, existential generalization (also known as existential introduction, ∃I) is a valid rule of inference that allows one to move from a specific statement, or one instance, to a quantified generalized statement, or existential proposition. In first-order logic, it is often used as a rule for the existential quantifier (∃) in formal proofs. Example: "Rover loves to wag his tail. Therefore, something loves to wag its tail." In the Fitch-style calculus: : Where ''a'' replaces all free instances of ''x'' within ''Q''(''x'').〔pg. 347. Jon Barwise and John Etchemendy, ''Language proof and logic'' Second Ed., CSLI Publications, 2008.〕 == Quine == Universal instantiation and Existential Generalization are two aspects of a single principle, for instead of saying that "∀''x'' ''x''=''x''" implies "Socrates=Socrates", we could as well say that the denial "Socrates≠Socrates"' implies "∃''x'' ''x''≠''x''". The principle embodied in these two operations is the link between quantifications and the singular statements that are related to them as instances. Yet it is a principle only by courtesy. It holds only in the case where a term names and, furthermore, occurs referentially.〔 Here: p.366.〕 抄文引用元・出典: フリー百科事典『 ウィキペディア(Wikipedia)』 ■ウィキペディアで「Existential generalization」の詳細全文を読む スポンサード リンク
|